2004
DOI: 10.1080/10284150400020516
|View full text |Cite
|
Sign up to set email alerts
|

The Hypothalamic-Pituitary-Adrenal Axis in the Neuroendocrine Regulation of Food Intake and Obesity: The Role of Corticotropin Releasing Hormone

Abstract: The aim of this paper is to review the present knowledge on the role of the hypothalamic-pituitary-adrenal axis in the control of food intake and the pathogenesis of obesity and to discuss, on the basis of available literature, the interactions between other neurosystems and this hormonal axis. Food intake is influenced by a system of physiologic signals and behavioral controls consisting of positive and negative sensory feedback mechanisms. It is regulated by a complex neuroendocrine system consisting of peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(57 citation statements)
references
References 79 publications
(78 reference statements)
1
53
0
3
Order By: Relevance
“…In addition to its role in controlling the activity of the pituitary adrenal axis, CRH controls the food intake too. Within the brain, CRH with its two receptor types, CRH type 1 (CRH1-R) and CRH type 2α (CRH2α-R), its binding protein, and its closely related peptide urocortin, forms a network of neuronal pathways that is capable of interacting with other circuitries controlling the food intake (Mastorakos and Zapanti 2004). It has been shown that CRH mediates the anorexigenic eff ect of α-MSH in fi sh (Matsuda et al 2008) and ELABELA in the adult mouse (Santoso et al 2015).…”
Section: Th E Hypothalamus Role In the Food Intake Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its role in controlling the activity of the pituitary adrenal axis, CRH controls the food intake too. Within the brain, CRH with its two receptor types, CRH type 1 (CRH1-R) and CRH type 2α (CRH2α-R), its binding protein, and its closely related peptide urocortin, forms a network of neuronal pathways that is capable of interacting with other circuitries controlling the food intake (Mastorakos and Zapanti 2004). It has been shown that CRH mediates the anorexigenic eff ect of α-MSH in fi sh (Matsuda et al 2008) and ELABELA in the adult mouse (Santoso et al 2015).…”
Section: Th E Hypothalamus Role In the Food Intake Controlmentioning
confidence: 99%
“…A defect in the synthesis and release of the CRH has been implicated in the development of the obesity in laboratory animals (Mastorakos and Zapanti 2004). Moore et al (2015) have reported a benefi cial eff ect of CRH1-R antagonism in the attenuation of the stress-induced consumption of palatable diets in female rhesus monkeys.…”
Section: Th E Hypothalamus Role In the Food Intake Controlmentioning
confidence: 99%
“…In addition, the stimulation of the arcuate nucleus secretion of the orexigenic neuropeptide Y (NPY) concomitantly enhances the CRH release, probably in order to counter-regulate its own actions, and also inhibits the locus coeruleus/norepinephrine sympathetic system and activates the parasympathetic system, in order to decrease thermogenesis and enhance the digestion and storage of nutrients. Stress-induced suppression of NPY secretion, which abates its central orexigenic and anxiolytic actions, is also likely to be involved in the anorectic phase during acute stress [87] .…”
Section: The Different Eating Behaviours Of the Patientsmentioning
confidence: 99%
“…Nixon et al, 2002). It is also interesting to note the involvement of the HPA axis and similar signalling proteins in appetite regulation and control of body composition at sites outwith the hair follicle (Mastorakos and Zapanti, 2004).…”
Section: Biology Of Pigment Productionmentioning
confidence: 99%